Utilization of Social Media as a Digital Publication Strategy at Nurul Ulum Islamic Boarding School - Indrioko, Erwin (Letiges, 2023)
Social media is essential for introducing Islamic educational institutions to the broader community. The presence of social media is beneficial and provides benefits for Islamic educational institutions in the digital publication of the educational services offered. This study aims to describe the use of social media as an effort for digital publications carried out by the Nurul Ulum Islamic boarding school Blitar City. This research uses a qualitative approach, and this type of research is descriptive. This study's data sources were Islamic boarding school caretakers, public relations schools, teaching boards, and administrative staff. This study used several data collection methods: participatory observation methods, in-depth interview methods, and documentation methods. The data analysis technique used is; data reduction, data presentation, and conclusion. The study's results stated that the types of social media users at the Nurul Ulum Islamic boarding school included Facebook, Instagram, TikTok, and YouTube. This research shows that YouTube is a social media often used as a digital publication. The purpose of using social media at the Nurul Ulum Islamic boarding school is as a medium of communication, media for promotion, and media to build institutional brands. The real implication of using social media is that the wider community increasingly recognizes the Nurul Ulum Islamic boarding school, the number of students is increasing yearly and has received broad public trust.